2018
DOI: 10.1017/pasa.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Light Curve Solutions of Ultrashort-Period Eclipsing Binaries

Abstract: Photometric observations in V and I bands and low-dispersion spectra of ten ultrashort-period binaries (NSVS 2175434, NSVS 2607629, NSVS 5038135, NSVS 8040227, NSVS 9747584, NSVS 4876238, ASAS 071829-0336.7, SWASP 074658.62+224448.5, NSVS 2729229, NSVS 10632802) are presented. One of them, NSVS 2729229, is newly discovered target. The results from modeling and analysis of our observations revealed that: (i) Eight targets have overcontact configurations with considerable fillout factor (up to 0.5) while NSVS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…We should declare that the parameters of the spot were set as fixed, during third light search, in order to quickly determine a convergent solution. The final T 1 and T 2 were determined by the following equations (Coughlin et al 2011;Kjurkchieva et al 2018a),…”
Section: Analyzing the Light Curvesmentioning
confidence: 99%
“…We should declare that the parameters of the spot were set as fixed, during third light search, in order to quickly determine a convergent solution. The final T 1 and T 2 were determined by the following equations (Coughlin et al 2011;Kjurkchieva et al 2018a),…”
Section: Analyzing the Light Curvesmentioning
confidence: 99%
“…Their result declared that unlike secondary components, the primary components of cool contact binaries follow the MRR of MS stars. Another study by Kjurkchieva et al (2018) found that the calculated mass-luminosity relation is not as precise as the mass-radius relation in the selected sample of 10 ultrashort-period overcontact binaries. Li et al (2020) in a statistical study of 380 Kepler contact binary systems found that the linear MRR of the primary and secondary stars is identical and that the primary stars are found generally on the ZAMS line.…”
Section: (1)mentioning
confidence: 90%
“…Actually, this average value is neither the primary's nor the secondary's, it should be a quadrature temperature of the two components. Therefore, when modeling the light curves of these systems, we set this temperature as the primary's (primary means the hotter component), T 1 = T m , and the final temperatures of the primary and secondary components were derived by using the following equations (Kjurkchieva et al 2018):…”
Section: Photometric Solutionsmentioning
confidence: 99%
“…The orbital period investigation (Lohr et al 2013a;Koen 2014) of 1SWASP J234401.81−212229.1 has proved that it is a hierarchical multiple-star system. In order to check whether 1SWASP J074658.62+224448.5 and 1SWASP J075102.16+342405.3 exhibit cyclic variation in the orbital period, we reanalyzed their O −C diagrams by using all the available eclipsing times including the data of NSVS, SuperWASP, CSS, ASAS-SN, Jiang et al (2015aJiang et al ( , 2015b, and Kjurkchieva et al (2018). Using the same linear ephemerides those given by Jiang et al (2015aJiang et al ( , 2015b, we calculated the O −C values of the two systems and constructed the O − C diagrams displayed in Figure 6.…”
Section: Statistics On Well-studied Uspcbs With Orbital Period Variat...mentioning
confidence: 99%